Vascular Calcifications in Homozygote Familial Hypercholesterolemia - Awan, Z; Alrasadi, K; Francis, G A.; Hegele, R A.; McPherson, R; Frohlich, J; Valenti, D; de Varennes, B; Marcil, M; Gagne, C; Genest, J; Couture, P (Arteriosclerosis, thrombosis, and vascular biology, 2008)
BACKGROUND—Patients with homozygous familial hypercholesterolemia (hmzFH) attributable to LDL receptor gene mutations have shown a remarkable increase in survival over the last 20 years. Early onset coronary heart disease (CHD) and calcific aortic valve stenosis are the major complications of this disorder. We now report extensive premature calcification of the aorta in patients with hmzFH. METHODS AND RESULTS—We examined 25 hmzFH patients from Canada; mean age was 32 years (range 5 to 54), and mean baseline cholesterol before treatment was 19±5 mmol/L (737±206 mg/dL). Aortic calcification was quantified using computed tomography (CT). An elevated mean calcium score was found in patients by age 20 and correlated with age (r=0.53, P=0.001). One quarter (24%) of patients underwent aortic valve surgery. CONCLUSIONS—We document premature severe aortic calcifications in all adult hmzFH patients studied. These presented considerable surgical management challenges. Strategies to identify and monitor aortic calcification in hmzFH by noninvasive techniques are required, as are clinical trials to determine whether additional or more intensive therapies will prevent the progression of such calcifications. Whether vascular calcifications in hmzFH subjects are related to sustained increases in LDL-C levels or to other mechanisms, such as abnormal osteoblast activity, remains to be determined.